Immunoexpressions of e-cadherin and P-catenin and association with tumour Grading in primary ovarian carcinoma in Hospital univers1ti sains malaysia, Kelantan - Hassan, Aniza (2012)
Immunoexpressions of E-cadherin and P-catenin and correlation with tumour grading in primary ovarian carcinoma in Hospital Universiti Sains Malaysia, Kelantan. E-cadherin and 0-catenin, cell adhesion molecules(CAM's) are shown to be involved in tumour progression. This study aims to analyze immunoexpression of E-cadherin and fi-catenin in surface epithelial ovarian carcinoma and evaluate its association with histological subtype, tumour grade and other important clinicopathological parameters. Tissue sections were obtained from archival blocks from HUSM for the duration of 13 years from 1998 to 2010. Expressions of both markers were analyzed immunohistochemically in 88 patients on paraffinized tissues. The tumor was evaluated and scored in hot spots according to intensity and proportion of cells stained. Expression was categorized as either positive or negative using median as cutoff positivity for statistical analysis. E-cadherin and P-catenin were variably expressed by tumour cells. The distribution of both markers was skewed (E-cadherin - mean 49.17, standard deviation 33.342, median 50.00; P-catenin -mean 34.23, standard deviation 34.032, median 20.00). In 64.7% of high grade ovarian carcinoma, both E-cadherin and P-catenin expression were lost (p=0.026). The grade of serous carcinoma was significantly associated with negative expression of both E-cadherin and P-catenin, in which 90.0% of the high grade cases lost expression of both markers(p=0.004). In early FIGO stage(FIGO I and II), 27.8% of cases had lost expression of both markers, whereas 72.2% of the patients maintained expression of one of the markers(p=0.037). This association was not seen in advanced FIGO stage. No significant association between E-cadherin and P-catenin expressions and age, race, peritoneal deposits and capsular breach(p>0.05) were observed. Ovarian carcinomas with loss of expression of both E-cadherin and P-catenin might behave more aggressive clinically as they tend to have higher grade and stage.